The Relationship Between Emotional Intelligence and Learning Achievement of Grade IV Elementary School Students - Sentia, Rani; Ifrianti, Syofnida; Erfayliana, Yudesta (Program Studi PGMI, Universitas Al Falah As Sunniyah Kencong Jember, 2025)
Students with low emotional intelligence often have difficulty controlling emotions, dealing with academic pressure, and adapting to the school environment, which can ultimately affect their academic achievement. Grade IV students on average have emotional intelligence moderate, so it is necessary to conduct research to determine the relationship between emotional intelligence and student learning achievement in class IV. The research method used in this study uses a quantitative approach with a correlation research type. The population in this study was all grade IV of SDN 1 Wayhalim Permai. A total of 20 students. The data collection tools used were questionnaires to find emotional intelligence data and documentation to find learning achievement data. The prerequisite tests used were normality tests and linearity tests. The data analysis technique in this study used the Pearson correlation test (product moment correlation). Based on the research, the results showed that there was a significant relationship between students' emotional intelligence and the learning achievement of grade IV students.